Effective Relationships Between Younger Caregivers and Older Care Recipients Across a Continuum of Formal Residential Care Settings: A Scoping Review and a Critical Analysis - Carol-Ann Dixon; Vera Roos; Matthews Katjene; Jaco Hoffman; Jaco Hoffman (Frontiers Media S.A., 2024)
Objective: This article aims to conduct a scoping review of what constitutes effective relational interactions between caregivers (CGs) and older persons (OPs) across formal residential care settings.Methods: A scoping review of publications between January 2000 and December 2021 yielded 10,929 articles, and after removing duplicates and applying exclusion criteria, 36 articles were analysed.Results: Articles were scrutinised for interactions involving both CGs and OPs, using a thematic framework analysis to identify effective relational constructs. Four themes emerged: 1) Diverse perspectives on the same context: for OPs it is home, and for CGs, workplace. 2) CGs move for a one-up position and OPs submit to a one-down, or as friends. 3) Relational qualities have been mostly associated with CGs, confirming care as a unidirectional action 4). Relationships between CGs and OPs result either in effective or ineffective care outcomes.Conclusion: The dual meanings attached to the same context limit the authentic interactions between CGs and OPs. We propose a relational caregiving approach by considering the interactions of both CGs and OPs, changing the relational definition, and demonstrating effective relational qualities.